The Effectiveness of Differentiated Learning in Text Learning Review Language Indonesia in Era Digital in class X of Muhammadiyah 1 High School, Unismuh Makassar - Indriani Indriani; Rosmini Madeamin; Akram Budiman Yusuf (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study is to determine the effectiveness of the differentiated learning model to be applied in class. By conducting research in class X Muhammadiyah High School 1 Unismuh Makassar. Problem main In this study, there is a lack of interest in learning for students so that the learning process is less effective and students feel bored and fed up. If the learning that is often used by teachers is only based on one model learning only such as one of the group discussion methods, then students will not be able to hone their abilities and creativity during the learning process. This type of research is quantitative research with a quasi-experimental design . The form of research design with pretest-posttest. By using the entire population from 2 class Which become object study X A class experiment as many as 18 students and XB control class as many as 16 students. The results of the study the average value of class XA as the experimental class was 69.83 while class XB as the control class was 65.43. Then the average post-test value of class XA was 89.27 while class XB was 86.18 this shows that the post-test of the Experimental class is higher than the control class, thus proving the learning model differentiate effective For learning Language Indonesia in class X of Muhammadiyah 1 High School, Unismuh Makassar.